Factors Affecting the Implementation of Early Growth Stimulation, Detection, and Intervention by Midwives - Fetty Wijaya; Nia Kania; Roselina Panghiyangani; Mohammad Bakhriansyah; Harapan Parlindungan Ringoringo (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2025)
Early growth stimulation, detection, and intervention (EGSDI) activities are crucial for identifying fetal growth deviations. In Kotabaru Regency, South Kalimantan, Indonesia, EGSDI achievement falls below target. This cross-sectional study analyzed factors affecting EGSDI implementation by midwives. Seventy-four midwives were surveyed regarding their knowledge, attitude, and motivation towards EGSDI, and their implementation of these activities. Chi-square tests revealed significant associations between EGSDI implementation and midwives' knowledge (p=0.000), attitude (p=0.001), and motivation (p=0.001). Multinomial logistic regression showed knowledge as the strongest predictor (p=0.001, OR=32.98), followed by motivation (p=0.004, OR=13.26) and attitude (p=0.047, OR=5.47). The study concludes that midwives' knowledge, attitude, and motivation significantly influence EGSDI implementation, with knowledge being the predominant factor. Enhancing midwives' knowledge should be prioritized to improve EGSDI implementation in this region, potentially improving maternal and child health outcomes in Indonesia.